2017
DOI: 10.1177/1049732317717695
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Providing Postpartum Education in Dar es Salaam, Tanzania: Narratives of Nurse-Midwives and Obstetricians

Abstract: Postpartum education can save lives of mothers and babies in developing countries, and the World Health Organization recommends all mothers receive three postpartum consultations. More information is needed to better understand how postpartum education is delivered and ultimately improves postpartum health outcomes. The purpose of this qualitative study was to examine how postpartum care was delivered in three postnatal hospital clinics in Dar es Salaam, Tanzania. Semistructured interviews with 10 nurse-midwiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Health providers, including midwives, must constantly navigate and manage the cultural expectations and pressures of their roles, institutions, and that of the external societies from which they and their patients originate. Previous research has observed this challenge among maternal health specialists as well as those providing treatment for SDV in hospital-based settings in LMIC (Mselle et al, 2017;Senarathna, Hunter, Dawson, & Dibley, 2013). Midwives, being female, have all been socialized into the same cultural and gender norms as the women they described, with a powerful internalized sense of what it is to be a respectable woman in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…Health providers, including midwives, must constantly navigate and manage the cultural expectations and pressures of their roles, institutions, and that of the external societies from which they and their patients originate. Previous research has observed this challenge among maternal health specialists as well as those providing treatment for SDV in hospital-based settings in LMIC (Mselle et al, 2017;Senarathna, Hunter, Dawson, & Dibley, 2013). Midwives, being female, have all been socialized into the same cultural and gender norms as the women they described, with a powerful internalized sense of what it is to be a respectable woman in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…56 Nursesmidwives also recognised their lack of time for providing health education to new mothers or even providing essential life-saving practices to mothers/newborns because of staff shortages. 59 Another recurring theme that women mentioned as having profound effect on their health-seeking patterns was the lack of privacy during the visits. 57 58 In some articles, women expressed concerns about sharing confidential information because they felt that other people could listen into their interactions with health providers and questioned healthcare providers' ability to protect BMJ Global Health the confidentiality of the information they exchanged.…”
Section: Danda During Previous Contacts With Health Systemmentioning
confidence: 99%
“…55 59 63 68 While some healthcare workers agreed that family members needed to be included in post-delivery education, they often mentioned restrictions on this practice due to space constraints or other infrastructural issues. 59 This, in conjunction with traditional gender norms and cultural beliefs, led to most men perceiving maternal and newborn care as a 'feminine' domain, disengaging themselves from the process of care. 59 63 68 Both men and women acknowledged that, even if healthcare is perceived as the responsibility of the woman, men still exercised their power by either permitting or restricting women's access to services, through financial control or other forms of domestic violence.…”
Section: Male Involvement and Gender Dynamicsmentioning
confidence: 99%
“…However, due to the healthcare provider shortage, it is extremely difficult to create an opportunity for mother‐centred care, as healthcare providers are overworked and struggle under a larger than average patient load (Kohi et al, ; Shemdoe et al, ). Postnatal nurses in Dar es Salaam have reported that although women are supposed to remain in the health facility for 24 h, often times they are discharged within 6 h (Mselle et al, ). This limited time with mothers has been acknowledged by postnatal nurses as a challenge of sharing postnatal information with mothers (Mselle et al, ).…”
Section: Human Resources For Health Crisis For Newborn Care In Tanzaniamentioning
confidence: 99%
“…Postnatal nurses in Dar es Salaam have reported that although women are supposed to remain in the health facility for 24 h, often times they are discharged within 6 h (Mselle et al, ). This limited time with mothers has been acknowledged by postnatal nurses as a challenge of sharing postnatal information with mothers (Mselle et al, ). This results in a difficult challenge for the Tanzanian healthcare system even though there is a push to reduce neonatal mortality and provide women‐centred care.…”
Section: Human Resources For Health Crisis For Newborn Care In Tanzaniamentioning
confidence: 99%